Gyires Béla élete és tudományos munkássága - Virágos, Márta (Gerundium, 2023)
THE LIFE AND WORK OF BÉLA GYIRES. he research activities of the professor emeritus of the University of Debrecen, and one of the doyens of Hungarian mathematicians included the matrix theory, linear algebra, probability theory, and mathematical statistics. He was one of those outstanding mathematician who did not draw a rigid line between applied and theoretical mathematics. His most important and widely known results were int he ield of linear statistics. Many of his achievements are cited in books and textbooks.